The canine vaginal microbiome during heat and fertility in healthy breeding dogs - Anna Sophia Leps; Eva-Maria Packeiser; Christina Schwens; Benjamin Stoelcker; Semir Doric; Martina Wirkner; Beate Walter; Axel Wehrend; Viktoria Kichmann; Klaus Jung; Sandra Goericke-Pesch (PLoS ONE, 2025)
A healthy and balanced vaginal microbiome is often thought to be an important prerequisite for successful breeding and healthy litters. Previous studies investigating the influence of canine vaginal bacteria on fertility mostly relied on aerobic culturing. In recent years, culture-independent methods, such as next-generation sequencing (NGS), have become popular. With the ability to analyze the microbiome as a whole, research in this field has made notable advances. This is the first study to correlate NGS data of the canine vaginal microbiome in heat with fertility data. Healthy breeding bitches (n=80) presented for routine pre-breeding examination were sampled during early heat and mated after ovulation. A vaginal sample was taken for NGS analysis and microbiological culture. Additionally, a blood sample was collected. Fertility data (mating, pregnancy, delivery, litter size) were assessed. NGS revealed a diverse microbiome in all the samples. Bioinformatics and statistical analysis did not provide evidence of larger differences in the microbiome of those bitches that became pregnant and those that did not.